Evaluasi Program Pendidikan Karakter dengan Menggunakan Model Goal Oriented Evaluation di SD Santo Fransiskus Sragen - Renata Octaviani, Agnes; Astuti, Suhandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the implementation of the 7S Movement Program at Santo Fransiskus Elementary School in Sragen using the Goal Oriented Evaluation Model. The research uses an evaluative approach with data collection techniques through observation, questionnaires, and interviews. The results show that all aspects of the evaluation are in the excellent category, indicating that the program is running effectively and that the evaluation model used is proven to be applicable in assessing character education programs based on habits in elementary schools. Based on the seven steps of goal-oriented evaluation, the general objectives of the program were clearly and contextually formulated and rooted in the spiritual values of St. Francis, with an 88% achievement rate for the formulation of objectives, which is categorized as excellent. The classification of targets obtained a percentage of 83.4% (excellent). The formulation of objectives in the form of observable behavior showed an average of 76.26% for students and 90.3% for teachers. The determination of achievement indicators reached an average of 85.60% for students and 87.16% for teachers, reinforced by the results of observations of polite, courteous, and friendly behavior. The selection and development of measurement methods were rated as very good with valid and reliable instruments. The collection of relevant data showed high suitability with the school's needs, while the comparison of implementation results with program objectives reached 90.64% in the very good category.These findings confirm that the 7S Movement Program is effective in shaping the character of students and should be maintained and developed as a model for character building in elementary schools.